Mexico : Broadening Access to Financial Services Among the Urban Population, Mexico City's Unbanked, Volume 2, Annexes - World Bank (Washington, DC, 2012)
The present report looks at issues of access to financial services in urban Mexico, drawing on existing documentation as well as on research (surveys, interviews and focus groups) carried out in Mexico City during 2002. The motivation behind this interest in financial exclusion is two fold. First, it is well documented that being "unbanked" (excluded from access to financial services) has costs; and it makes it more expensive to engage in a number of transactions (paying and being paid) and more difficult to save while maintaining the value of an asset As such, higher access to financial services is desirable from an efficiency point of view. Second, financial exclusion is an issue that primarily affects the poor. Access to financial services can help with poverty alleviation, particularly to the extent that it encourage asset buildings and help cope with shocks and overcome liquidity constraints. The report focuses on two key questions: what are the benefits the unbanked (those excluded from financial services) could gain from using formal financial sector institutions; and what discourages them from doing so. The objective is to help to identify measures to increase access to financial services in Mexico. As such the report is organized as follows. Chapter 1 sets the stage by discussing the importance of access to financial services and what other countries are doing to promote such access. Chapter 2 presents an analysis of actual and potential demand for financial services, and offers a profile of the unbanked residents of Mexico City. Chapter 3 then looks at the supply of financial services by the formal financial sector and possible explanations for Mexico's extremely low rate of financial access. Chapter 4 concludes and discusses possible means of improving financial participation.